In-vitro effects of different hyaluronic acids on periodontal biofilm-immune cell interaction - Zhu, Xilei; Sculean, Anton; Eick, Sigrun (Frontiers in Cellular and Infection Microbiology, 2024)
Introduction Recent studies have demonstrated a positive role of hyaluronic acid (HA) on periodontal clinical outcomes. This in-vitro study aimed to investigate the impact of four different HAs on interactions between periodontal biofilm and immune cells. Methods The four HAs included: high-molecular-weight HA (HHA, non-cross-linked), low-molecular-weight HA (LHA), oligomers HA (OHA), and cross-linked high-molecular-weight HA (CHA). Serial experiments were conducted to verify the influence of HAs on: (i) 12-species periodontal biofilm (formation and pre-existing); (ii) expression of inflammatory cytokines and HA receptors in monocytic (MONO-MAC-6) cells and periodontal ligament fibroblasts (PDLF) with or without exposure to periodontal biofilms; (iii) generation of reactive oxygen species (ROS) in MONO-MAC-6 cells and PDLF with presence of biofilm and HA. Results The results indicated that HHA and CHA reduced the bacterial counts in a newly formed (4-h) biofilm and in a pre-existing five-day-old biofilm. Without biofilm challenge, OHA triggered inflammatory reaction by increasing IL-1β and IL-10 levels in MONO-MAC cells and IL-8 in PDLF in a time-dependent manner, whereas CHA suppressed this response by inhibiting the expression of IL-10 in MONO-MAC cells and IL-8 in PDLF. Under biofilm challenge, HA decreased the expression of IL-1β (most decreasing HHA) and increased IL-10 levels in MONO-MAC-6 cells in a molecular weight dependent manner (most increasing CHA). The interaction between HA and both cells may occur via ICAM-1 receptor. Biofilm stimulus increased ROS levels in MONO-MAC-6 cells and PDLF, but only HHA slightly suppressed the high generation of ROS induced by biofilm stimulation in both cells. Conclusion Overall, these results indicate that OHA induces inflammation, while HHA and CHA exhibit anti-biofilm, primarily anti-inflammatory, and antioxidant properties in the periodontal environment.